PBL-Based Online Worksheet on Green Chemistry to Enhance Students’ Literacy and Numeracy Skills - Titi Sumanti; Abdul Gani; Yusrizal Yusrizal; Ibnu Khaldun; Sri Winarni; Putri Nabilah (Jurnal Pemberdayaan Masyarakat, 2025)
The limited availability of digital learning tools that effectively integrate green chemistry concepts while enhancing scientific literacy and numeracy presents a challenge in science education. Chemistry learning that integrates environmental issues, particularly the concept of green chemistry, requires contextual and innovative teaching materials to support the enhancement of students' scientific literacy and numeracy skills. This study aimed to develop a problem-based learning (PBL) online student worksheet on green chemistry to enhance students' scientific literacy and numeracy. The research employed a research and development (RD) approach using the ADDIE model and involved 24 randomly selected students from SMA Negeri 4 Lhokseumawe. Data were collected using expert validation sheets, student response questionnaires, and pre- and post-test instruments. The validation results indicated that the online worksheet was highly feasible (media: 96.88%, content: 96.39%, Aiken's V = 0.95). User responses were very positive (82.42%), and the questionnaire instruments demonstrated high validity (Aiken's V = 0.97). The N-Gain scores revealed moderate improvement in both scientific literacy (0.6061) and numeracy (0.6106), reflecting strengthened critical thinking, data interpretation, and problem-solving skills. This study contributes by providing a replicable model of an online worksheet that integrates environmental issues into chemistry learning, enriches digital learning resources, and supports the mastery of 21st-century competencies in science education. Therefore, the development of this PBL-based online student worksheet is considered feasible, practical, and effective in enhancing students' scientific literacy and numeracy skills.